Pengaruh Leverage, Profitabilitas, Ukuran Perusahaan dan Likuiditas terdahap Agresivitas Pajak: Studi Empiris pada Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia 2019-2024 - Zulmaizar, Muhammad; Hendrawan, Agus (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The Influence of Leverage, Profitability, Company Size and Liquidity on Tax Aggressiveness in Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange for the 2019-2023 Period. Thesis of the Accounting Study Program, Faculty of Economics and Business, Muhammadiyah University of Jakarta. This study aims to determine the effect of Leverage, Profitability, Company Size and Liquidity on Tax Aggressiveness in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The type of research used is quantitative research. The data used is secondary data. The population is 43 companies and the sampling technique uses the purposive sampling method. A sample of 14 companies x 5 years = 70 financial report data was obtained. The data analysis technique used is the panel data regression analysis technique using Eviews 10. The results of this study indicate that the Leverage variable has a positive and significant effect on Tax Aggressiveness. The Profitability variable has a negative and significant effect on Tax Aggressiveness. The Company Size variable has a positive and insignificant effect on Tax Aggressiveness. The Liquidity variable has a positive and insignificant effect on Tax Aggressiveness.